A systematic review with meta-analysis and indirect comparison of the results of studies evaluating the efficacy and safety of ceftobiprole and ceftaroline in adult patients in the treatment of infections of various localizations - Yu. M. Gomon; A. S. Petrichenko (Реальная клиническая практика: данные и доказательства, 2025)
Objective. To compare the efficacy and safety of fifth-generation cephalosporins (ceftaroline fosamil and ceftobiprole) when used in adult in the treatment of infections of various localization.   Materials and methods. A systematic review of the literature was conducted with a meta-analysis and indirect comparison of the results of studies evaluating the efficacy and safety of ceftobiprole and ceftaroline in adult patients in the treatment of community-acquired pneumonia, as well as skin and soft tissue infections based on the following outcomes: clinical cure rate, frequency of microbiological eradication, mortality, incidence of serious adverse events, the frequency of adverse events (AE), according to researchers, associated with taking the investigational drug (IP), as well as the frequency of diarrhea with the calculation of the odds ratio (OR) of the development of each of the events.   Results. The systematic review included 12 randomized clinical trials. In the treatment of community-acquired pneumonia, ceftobiprole was also effective in terms of clinical cure, mortality, and microbiological eradication, as ceftaroline and the combination of ceftriaxone with or without linezolid. In the treatment of complicated skin and soft tissue infections, ceftobiprole was comparable to ceftaroline and the combination of beta-lactam and vancomycin in terms of clinical cure and mortality. In terms of the frequency of microbiological eradication, ceftobiprole was comparable to the combination of beta-lactam and vancomycin and was superior to ceftaroline (OR 1.65, 95 % CI 1.11; 2.44, p = 0.01). In the treatment of lower respiratory tract infections, complicated skin and soft tissue infections, and bacteremia, ceftobiprole was also safe in terms of the incidence of SAE (OR = 0.93; 95 % CI 0.71;1.22; p = 0.63) and the incidence of diarrhea (OR 1.23; 95 % CI 0.93;1.64; p = 0.13) as well as ceftaroline.   Conclusions. Ceftaroline fosamil and ceftobiprole are comparable in efficacy and safety in the treatment of patients with community-acquired pneumonia and complicated skin and soft tissue infections. In the group of patients with nosocomial pneumonia, only ceftobiprole was proven effective in reducing mortality compared with the combination of ceftazidime and linezolid.